2020
DOI: 10.1055/s-0040-1712131
|View full text |Cite
|
Sign up to set email alerts
|

Primary Dysmenorrhea: Assessment and Treatment

Abstract: Primary dysmenorrhea is defined as menstrual pain in the absence of pelvic disease. It is characterized by overproduction of prostaglandins by the endometrium, causing uterine hypercontractility that results in uterine muscle ischemia, hypoxia, and, subsequently, pain. It is the most common gynecological illness in women in their reproductive years and one of the most frequent causes of pelvic pain; however, it is underdiagnosed, undertreated, and even undervalued by women themselves, who accept it as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
103
0
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 29 publications
1
103
0
22
Order By: Relevance
“…At present, there are few qualitative studies [19][20][21][22] that describe and analyse the perspective and experience of young female students suffering from dysmenorrhea and how it influences their daily lives. Previous studies [19][20][21]23] have reported how dysmenorrhea limits women's daily life. Chen et al [19] reported that the effects of dysmenorrhea can include difficulty in sitting and walking, the need to adopt antalgic positions (sleeping in foetal position), absenteeism from university classes and/or work, abandonment of family responsibilities (accompanying children to school) and recreational activities.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are few qualitative studies [19][20][21][22] that describe and analyse the perspective and experience of young female students suffering from dysmenorrhea and how it influences their daily lives. Previous studies [19][20][21]23] have reported how dysmenorrhea limits women's daily life. Chen et al [19] reported that the effects of dysmenorrhea can include difficulty in sitting and walking, the need to adopt antalgic positions (sleeping in foetal position), absenteeism from university classes and/or work, abandonment of family responsibilities (accompanying children to school) and recreational activities.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of cyclooxygenase activity and prostaglandin synthesis are observed in women with dysmenorrhea [10]. Accordingly, nonsteroidal antiinflammatory drugs (NSAIDs), which inhibit the expression of cyclooxygenase enzyme involved in the synthesis of prostaglandin, are used as the first-line treatment of primary dysmenorrhea [11]. These drugs are effective in managing primary dysmenorrhea; however, treatment with NSAIDs is also associated with several side effects, such as stomach pain and heartburn, increasing the risk of stomach ulcer and gastrointestinal bleeding [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Oral contraceptives and nonsteroidal anti-inflammatory drugs (NSAIDs) have been prescribed as first choice of treatment in PDM [3,4]. However, these drugs have adverse effects, and their long-term effects are less than optimal.…”
Section: Introductionmentioning
confidence: 99%